2014
DOI: 10.3109/08958378.2014.902147
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin mitigates mitochondrial impairments induced by acute inhalation of combustion smoke in the mouse brain

Abstract: Context Acute inhalation of combustion smoke adversely affects brain homeostasis and energy metabolism. We previously showed that overexpressed neuroglobin (neuron specific globin protein) attenuates the formation of smoke inhalation-induced oxidative DNA damage, in vivo, in the mouse brain, while others reported protection by neuroglobin in diverse models of brain injury, mainly involving oxidative stress and hypoxic/ischemic insults. Objective To determine to what extent elevated neuroglobin ameliorates po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Several studies have demonstrated that Ngb reduces ROS generation, preserves mitochondrial ATP production, resets the level of mitochondrial cytochrome c , participates in mitochondrial-mediated cell death signaling, and acts as a regulator of signal transduction in the brain (Wakasugi et al, 2005; Yu et al, 2009; Antao et al, 2010; Yu et al, 2016). Moreover, other studies have reported that Ngb decreases mitochondrial damage, protects mitochondrial function, and improves neuronal apoptosis (Li et al, 2013; Gorgun et al, 2014; Lan et al, 2014). However, the detailed mechanisms of the neuroprotective effects between Ngb and mitochondrial proteins against the neurotoxicity of sevoflurane exposure remain to be further elucidated (Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have demonstrated that Ngb reduces ROS generation, preserves mitochondrial ATP production, resets the level of mitochondrial cytochrome c , participates in mitochondrial-mediated cell death signaling, and acts as a regulator of signal transduction in the brain (Wakasugi et al, 2005; Yu et al, 2009; Antao et al, 2010; Yu et al, 2016). Moreover, other studies have reported that Ngb decreases mitochondrial damage, protects mitochondrial function, and improves neuronal apoptosis (Li et al, 2013; Gorgun et al, 2014; Lan et al, 2014). However, the detailed mechanisms of the neuroprotective effects between Ngb and mitochondrial proteins against the neurotoxicity of sevoflurane exposure remain to be further elucidated (Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…This investigation is the first to analyze mitochondrial function in axons using the Seahorse XFe24 Analyzer. Though not designed for tissue, the Seahorse XFe Analyzer has been used to measure oxygen consumption rate in sections or explants of rat and mouse brain [11, 12] and mouse retina [13]; however, no one has yet utilized it to investigate glaucomatous ON. Therefore, we decided to use this method to analyze individual glaucomatous ONs and answer a fundamental question: Whether and how mitochondrial respiration is altered with glaucoma progression.…”
Section: Introductionmentioning
confidence: 99%
“…All procedures were conducted in accordance with mandated standards of humane care and were approved by the UTMB Animal Care and Use Committee. We have previously developed a survival model of acute inhalation of wood smoke for the un-anesthetized rodent (Lee et al 2005; Chen L et al 2007; Lee et al 2009; Lee et al 2010; Lee et al 2011; Gorgun FM et al 2014). Briefly, smoke was generated by smoldering aspen wood shavings (1.3 gram/min) and dispersed by a tube-mounted fan into connected 20-liter transparent mouse exposure chamber.…”
Section: Methodsmentioning
confidence: 99%